(untitled) (Global Journals of Research in Engineering, 2023)
Aircraft attendants are at a high risk of occupational injuries and illnesses leading to substantial compensation costs and staff shortages in the aviation industry To address this issue this study introduces an innovative virtual reality technique and advanced motion tracking system integrated with ergonomics tools to effectively evaluate the risk of musculoskeletal disorders MSDs among aircraft attendants during their routine tasks The study involved twenty-two participants who performed two common tasks opening closing the passenger door and lifting luggage from the floor and placing it into the overhead compartment The inappropriate postures were identified which resulted in excessive strainon the participants lower back By analyzing the impact of biomechanical variables such as object weight body height and trunk motion on the lower back the study provides valuable insights that can inform the development of safety training programs and real-time monitoring approaches for injury prevention Additionally this innovative technology can be applied to other occupational fields